Euthanasia dalam Perspektif Kaidah Fikih al-á¸Œararu LÄ YuzÄlu bi al-á¸Œarar - Bakry, Kasman; Patuti, Asnawati; Andi Nur Afifah Ikrimah (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
Eutanasia is an attempt, action and assistance carried out by a doctor intentionally accelerating the death of a person, which he estimates is nearing death with the aim of alleviating or freeing his suffering. This study aims to determine and understand the practice of Eutanasia in the perspective of the principle of fiqh al-á¸arar lÄ yuzÄlu bi al-á¸arar. The problems that the authors raise in this study are: First, how to apply Eutanasia in the perspective of medical ethics. Second, how is the concept of the principle of fiqh al-á¸araru lÄ yuzÄlu bi al-á¸arar. Third, what is the position of Eutanasia in the perspective of the rules of al-larar lÄ yuzÄlu bi al-á¸arar. To get answers to these problems, the authors use descriptive qualitative (non-statistical) research that focuses on the study of texts and texts. And using the method of historical, juridical-ormative and philosophical approaches. The research results found are as follows; First, Eutanasia is contrary to the medical code of ethics, although this practice is applied in several countries through procedures and requirements that must be met. The two harms must be removed but cannot be eliminated by the other harm. Third Eutanasia is divided into two, namely active Eutanasia and passive Eutanasia. Active Eutanasia of scholars agree that the law is haram, whereas passive Eutanasia there are differences in ulama in it.